Inventory on Deciphering Interiors of Commercially Important Indian Trees Using 3D Electric Resistance Tomograph (ERT) - Divakara, B. N.; Nikhitha, C. U.; Chauhan, S. S. (Indian Forester, 2020)
Tree Tronic tomograms are one among the advanced non-destructive method aiding for tree inspection. This method gives high resolution with more precision in measuring the sapwood, heartwood, stress and decay in the living trees. Our study focused on understanding the internal wood structural details using 3D images of Electric Resistance Tomograph (ERT) for commercially important tree species viz. Santalum album L. (Sandalwood) and Pterocarpus santalinus L.f. (Red sandalwood/sanders) of India. Initially, using ERT, the tree resistivity offered across the crosssections of the stems at different heights from the ground was recorded. The combined effect of moisture content in the sapwood and resistivity offered by heartwood presented a non-invasive 2D cross sectional images at each height with color differentiation from blue (low resistance) to brown (high resistance). In the healthy trees the concentric ring structure and the compactness of the wood at the center offered maximum resistance and gradually decreased towards the bark. However, 2D images failed to give the overall scenario of the structural details at different heights of tree stem. Hence, the 2D images of the individual trees were placed in the descending order with respect to the height measurements from the ground to give 3D images. The 3D imagery demonstrated in our study depicts the effective mode of representing the resistivity distribution along the stem to further differentiate the sapwood and heartwood in the standing tree.